Voice onset time (VOT) consonants realization of Indian-Muslim English speakers in Malaysia / Nazirul Mubin Mohd Noor ...[et al.] - Anuar, Nuramira; Yusof, Ahmad Muhyiddin; Abdul Rahim, Puteri Rohani Megat; Janah Singh, Daljeet Singh Sedhu; Mohd Noor, Nazirul Mubin (Universiti Teknologi MARA, 2021)
Voice Onset Time (VOT) is commonly found in most spoken languages. It is a speech feature to indicate differences in voicing and meaning. In particular, the duration of Voice Onset Time values is directly determined by place of articulation, with labial VOT values being shorter than velar and alveolar and, some-times, alveolar being shorter than velar. In the present study, the researchers examined the VOT values of English speakers in Malaysia, particularly Indian-Muslim English speakers in the northwest region of Malaysia. From the analysis conducted by employing PRAAT software in examining differences in VOT values of voiced and voiceless plosives, the results revealed that there were significant differences in VOT values of bilabial plosives of /p/ and /b/ as well as alveolar plosives of /t/ and /d/ in Indian-Muslim English speakers' community. However, there is no significant difference in the VOT values of both voiced and voiceless velar plosives of /k/ and /g/, indicating the influence of the speakers' mother tongue in their English language use. In the case of prominence of aspiration in the present study, the results show that the Indian-Muslim English speakers in Malaysia have high VOT values in voiceless alveolar plosive /t/ (M = 0.0705, SD = 0.0509) and voiced alveolar plosive /d/ (M = 0.015, SD = 0.00). The findings highlight that there are differences in term of VOT values in bilabial plosives and alveolar plosives of English speakers between Indian-Muslim community and Malay community. In conclusion, this study can provide insights to other researchers, academia, linguists both in Malaysia and overseas to further about the VOT consonants realizations of Indian-Muslim English speakers in Malaysia as this group of speakers in the north-west region of Malaysia is exclusive in the Malaysian context.